Safety and feasibility of using acellular sterile filtered amniotic fluid as a treatment for patients with COVID-19: protocol for a randomised, double-blinded, placebo-controlled clinical trial. Issue 2 (11th February 2021) - Tonna, Joseph E; Pierce, Jan; Hatton, Nathan; Lewis, Giavonni; Phillips, John D; Messina, Alyssa; Skidmore, Chloe R; Taylor, Kirsten; Selzman, Craig H
Abstract : Introduction: Human amniotic fluid (hAF) has been shown to reduce inflammation in multiple experimental models. hAF has previously been approved by the US Food and Drug Administration (FDA) as a human cellular and tissue product for tissue injury for human administration, and used safely in thousands of patients as a therapeutic treatment for diverse conditions. Given the profound inflammatory response observed in patients with COVID-19, and the successful completion of 10-patient pilot study of intravenous hAF, we present a trial design for a larger clinical trial of intravenous hAF for the treatment of COVID-19. Methods and analysis: This paper describes the methodology of a phase I/II randomised, double-blinded, placebo-controlled clinical trial to determine the safety and feasibility of using acellular sterile filtered amniotic fluid as a treatment for patients with COVID-19. Primary outcome will be the change in C-reactive protein. Secondary outcomes include safety, biomarker inflammatory levels and clinically relevant outcomes at 30 days, including mortality, ventilator-free days and hospital and intensive care unit length of stay. Exploratory outcomes of health-related quality-of-life patient-reported outcomes will be collected. Hospitalised patients with laboratory-confirmed COVID-19 will be recruited. Ethics and dissemination: This study was approved by the University of Utah Institutional Review Board (IRB_0013292), approved by the US FDA under Investigational New Drug (No 23369) and is registered on ClinicalTrials.gov. Results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: NCT04497389 ; Pre-results.